An assessment of the classical relationship of price fluctuations between the gold market and the US Dollar. : Array - Neethling, Roan; Meyer, Daniel (Acta Universitatis Danubius. Œconomica, 2021)
For many decades the relationship between the gold market and the US dollar has dominated the international economy. In times of economic and policy uncertainty, the gold price traditionally increased, while in periods of growth and certainty, the US dollar usually appreciated in value compared to other currencies. This paper has the objectives to re-assess this classic relationship and to determine the causality between the gold market and the US currency. To achieve the objective of the study, a quantitative econometric methodology was utilised for the period 1995 to 2020. A Vector Autoregression model was estimated including three variables namely the gold market, US dollar index and real GDP for the US. Interesting relationships and causalities between the three variables were estimated including that the relationship between the gold market and real GDP seems stronger than the relationship between the gold market and the US dollar index. An important implication of this study is that changes in the gold price are not a significant indicator on its owns to track changes in the US currency. The value of the research is in the renewed analysis and updated coefficients on the long and short-run between the classic variables.